2019
DOI: 10.3354/meps12994
|View full text |Cite
|
Sign up to set email alerts
|

Extension of the growing season of phytoplankton in the western Baltic Sea in response to climate change

Abstract: Phenology of phytoplankton was investigated at a coastal station in the western Baltic Sea from 1988 to 2017 by means of microscopically determined biomass and chlorophyll a (chl a) data. The prolongation of the growing season in this marine area is much stronger than that known from terrestrial areas. The growing season, defined by biomass or chl a thresholds, increased by 125 or 129 d, respectively, and extends recently from February to December. The spring bloom started earlier at a rate of 1.4 d yr −1 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
37
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(41 citation statements)
references
References 50 publications
4
37
0
Order By: Relevance
“…In the southwestern Baltic Sea, the spring bloom has advanced by 1.4 d yr −1 and the growing season increased by 127 days between 1988 and 2017 (Wasmund et al 2019). The earlier start of the spring bloom was related to increased sunshine duration and the prolongation in autumn due to warmer seawater temperature.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…In the southwestern Baltic Sea, the spring bloom has advanced by 1.4 d yr −1 and the growing season increased by 127 days between 1988 and 2017 (Wasmund et al 2019). The earlier start of the spring bloom was related to increased sunshine duration and the prolongation in autumn due to warmer seawater temperature.…”
Section: Discussionmentioning
confidence: 96%
“…The number of days with sea surface temperature above 17°C almost doubled between 1983 and 2014 and between 1998 and 2013 both light attenuation and near-surface Chlorophyll a (Chl a) increased in the central Baltic Sea (Kahru et al 2016). Earlier, more prolonged spring blooms with lower average biomass during the past 20 years have been observed (Raateoja et al 2005;Groetsch et al 2016;Kahru et al 2016;Hjerne et al 2019;Wasmund et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…A phenomenon worth mentioning is the extension of the growing season of phytoplankton in the oceans (Gobler et al, 2017), but also in the Baltic Sea (Groetsch et al, 2016). The period with satelliteestimated chlorophyll a (chl a) concentrations of at least 3 mg m -3 has doubled from approximately 110 days in 1998 to 220 days in 2013 the central Baltic Sea (Kahru et al, 2016 Wasmund et al (2019) found an earlier start of the spring bloom with a rate of 1.4 days/year and a later end of the autumn bloom with 3.1 days/year and a corresponding extension of the growing season (Figure 10). The earlier start of the growing season was correlated with a slight increase in sunshine duration during spring whereas the later end of the growing season was correlated with a strong increase in water temperature in autumn.…”
Section: Phytoplankton Bloomsmentioning
confidence: 99%
“…The productive period is prolonged with increasing temperatures, already signified by the occurrence of earlier spring and later autumn phytoplankton blooms (Wasmund et al, 2019). This implies that more inorganic nutrients are intercepted, thereby enhancing the coastal filter efficiency.…”
Section: Efficiency Of the Coastal Filter In The Futurementioning
confidence: 99%